2010
DOI: 10.1063/1.3431608
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing magnetorheology with nonmagnetizable particles

Abstract: Experimental results illustrate an enhancement in the field-induced yield stress of magnetorheological (MR) fluids caused by the presence of nonmagnetizable particles. Particle-level simulations in three dimensions show similar behavior. However, the enhancement does not appear in simulations in which the spheres are confined to a monolayer. A mechanistic explanation of these observations is currently lacking. Nonetheless, the ability to enhance the MR response by replacing magnetizable particles with nonmagne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
45
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 11 publications
1
45
0
Order By: Relevance
“…Actually this kind of effect has been observed by D.J. Klingenberg et al: they found that adding a part of non magnetizable particles to magnetizable ones could notably increase the field induced yield stress 9 . Although not explained at this time the authors recently prove that it was due to a jamming effect induced by the magnetic field in the presence of a higher total volume fraction of particles 10 .…”
mentioning
confidence: 72%
“…Actually this kind of effect has been observed by D.J. Klingenberg et al: they found that adding a part of non magnetizable particles to magnetizable ones could notably increase the field induced yield stress 9 . Although not explained at this time the authors recently prove that it was due to a jamming effect induced by the magnetic field in the presence of a higher total volume fraction of particles 10 .…”
mentioning
confidence: 72%
“…9 A few years ago, Klingenberg et al reported interesting behavior that the yield stress of magnetorheological fluids was enhanced by the presence of nonmagnetizable particles. 10 This behavior presents us an idea that the nonmagnetic particle is able to participate in forming the chain structure. In this paper, this phenomenon was verified using a crosslinked hydrogel, and we discuss the replacement effect of magnetic particles with nonmagnetic particles.…”
mentioning
confidence: 99%
“…Sometimes the dispersion of non-magnetic particles in magnetic nanofluid is also known as inverse ferrofluid [16]. Recently experimentally enhanced field induced yield stress of magnetorheological (MR) fluid due to the presence of monodispersed nonmagnetizable glass particles of size 12 mm was studied [12]; the advantage of replacing magnetizable particles by nonmagnetizable particle being less expensive, less dense fluids, useful for more compact devices and more widespread commercialization of MR technology. de Gans et al [16] have also dispersed monodispersed silica spheres in an organic ferrofluid known as inverse ferrofluid and studied linear viscoelastic behavior as a function of frequency, magnetic field, and silica volume fraction with a specially designed magnetorheometer.…”
Section: Introductionmentioning
confidence: 99%
“…Under the effect of magnetic field, this fluid produces magnetoviscous effects [1][2][3][4][5][6][7][8][9][10][11]. Dispersion of micron size magnetic particles/ non-magnetic particles in magnetic nanofluids produces magnetorheological (MR) fluids [12][13][14][15][16][17][18]. Skjeltorp [18] started the pioneering work of dispersing non-magnetic particles in magnetic nanofluid and studied field induced structures and phase transitions of two dimensionally confined large non-magnetic particles in magnetic nanofluids.…”
Section: Introductionmentioning
confidence: 99%